2015
DOI: 10.1080/21565503.2015.1050415
|View full text |Cite
|
Sign up to set email alerts
|

Stuck between a rock and a hard place: the relationship between Latino/a's personal connections to immigrants and issue salience and presidential approval

Abstract: The Obama administration has simultaneously marketed the prospect of providing undocumented immigrants a pathway to citizenship through comprehensive immigration reform and overseen mass deportations of mostly Latino immigrants. While it is clear that immigration policy was highly influential to Latino voters in 2012, it remains unclear how this political hypocrisy is being interpreted by Latino voters. As deportations have risen steadily during the Obama administration, there has been little research on how d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…We use this measure as a proxy to gauge feelings of anxiety and concern about immigration enforcement that may be detrimental to individuals in their lives. Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). We expect that individuals who express high levels of concern about potential immigration enforcement will also be more likely to support immigrant rights activism.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…We use this measure as a proxy to gauge feelings of anxiety and concern about immigration enforcement that may be detrimental to individuals in their lives. Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). We expect that individuals who express high levels of concern about potential immigration enforcement will also be more likely to support immigrant rights activism.…”
Section: Methodsmentioning
confidence: 98%
“…Research has shown that immigration is a highly personal and salient issue to Latinos in part because of how it affects their families, neighbors, friends, and communities (Wallace 2012;Sanchez et al 2015). In fact, these types of personal social networks played a key role in motivating and mobilizing many Latinos to participate in the historic 2006 protest wave (Bloemraad and Trost 2008;Zepeda-Millan 2016).…”
Section: Immigration Racialization and Social Networkmentioning
confidence: 99%
“…Moreover, researchers do not find that having a loved one threatened by detention or deportation is politically alienating (Rocha, Knoll, and Wrinkle 2015; Vargas, Sanchez, and Valdez 2017), even as it shapes policy attitudes (Rocha, Knoll, and Wrinkle 2015; Sanchez et al 2015). The policy feedbacks literature suggests that when individuals view experiences with punitive policies as a result of their own poor choices or beyond their ability to affect change (both markers of alienation), they politically withdraw.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars refer to experiencing punitive policies vicariously via a loved one as proximal contact and demonstrate its political impact in the areas of criminal justice, healthcare, and welfare (Michener 2018; Soss and Schram 2007; Walker 2014). With respect to immigration, scholars find that among Latinos, proximal contact negatively impacts physical and mental health (Aranda, Menjivar, and Donato 2014; Pedraza, Nichols, and LeBrón 2017; Vargas, Sanchez, and Valdez 2017), and erodes trust in government and belief in the efficacy of political institutions (Rocha, Knoll, and Wrinkle 2015; Sanchez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, however, threat may prompt political demobilization and isolation. Sanchez et al (2015) showed that individuals who are close to an undocumented person prioritize immigration issues in making political decisions; however, such attention may not translate into political action. Threat may create risk-averse behaviors among racialized populations, hindering civic or political involvement.…”
mentioning
confidence: 99%